Exploring Three-Dimensional Technologies for Repatriation of Indigenous Cultural Heritage: The Case of the RUOKTOT Exhibition - Rauhala, Paula (UiT Norges arktiske universitet, 2024)
This master’s thesis explores the integration of three-dimensional (3D) technologies in RUOKTOT exhibition production in Sápmi, focusing on the reciprocal relationship between museums, 3D technologies, community, and heritage—narrated through the repatriation process of the famous Sámi drum, the goavddis of Paul-Ánde, widely known as Anders Poulsen, and digitization of old Sámi drums. The RUOKTOT exhibition was a 50th anniversary exhibition for Sámiid Vuorká-Dávvirat/The Sámi Museum in Karasjok (SVD). The exhibition was produced by SVD and opened in 2022. This exhibition focused on the multifaceted nature of the return of sacred Sámi drums, as valuable pieces of Sámi cultural heritage, Indigenous religion, historical context of sacred Sámi drums, the repatriation of the goavddis, and display of 3D digital representations of old Sámi drums. This research investigates foundational aspects of creating 3D digital representations of Sámi cultural heritage, including matters of access to and control over material culture and digital representations, and ethical considerations in the digitization processes of Indigenous cultural heritage. This work examines the applicability of 3D technologies in Sápmi in relation to repatriation context and critically analyses the politics inherent in heritage management. This project emphasizes cultural protocols surrounding digitization of Indigenous cultural heritage—a methodology often overlooked in existing guidelines. Through interviews and focus group discussions with 3D technology experts, heritage and museum professionals, valuable insights were gained into the management of Sámi cultural heritage, both locally and internationally, as well as the creation of 3D digital representations of old Sámi drums.